Menyemai Harmoni dalam Perbedaan: Spiritualitas Pentakostal sebagai Solusi Atas Polarisasi - Nurjadi Purnama; Setyobekti, Andreas Budi (EPIGRAPHE (Jurnal Teologi dan Pelayanan Kristiani), 2024)
Religious polarization in Indonesia presents a significant challenge in maintaining social harmony amidst cultural and religious diversity. This polarization is often triggered by doctrinal exclusivism, the politicization of religion, and the lack of interfaith dialogue. This study explores the contribution of Pentecostal spirituality, particularly through the concept of hospitality, as a solution to mitigate polarization. Using a qualitative descriptive approach, the research analyzes literature on the theology of religions, Pentecostal spirituality, and social dynamics related to religious conflicts. The analysis reveals that Pentecostal spirituality, centered on the role of the Holy Spirit as the source of love and acceptance, offers an inclusive approach that fosters equitable interfaith dialogue. The proposed theological model based on Pentecostal hospitality includes interfaith education, community strengthening through acts of love, inclusive doctrinal reinterpretation, and the creation of safe spaces for dialogue. This model is not only theoretically relevant but also practically applicable in pluralistic Indonesian society. With proper implementation, it has the potential to enhance social cohesion and provide a strategic solution for fostering sustainable interfaith harmony.